2019
DOI: 10.1002/cncr.32656
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐hematologist discordance in perceived chance of cure in hematologic malignancies: A multicenter study

Abstract: Background Ensuring that patients with hematologic malignancies have an accurate understanding of their likelihood of cure is important for informed decision making. In a multicenter, longitudinal study, the authors examined discordance in patients' perception of their chance of cure versus that of their hematologists, whether patient‐hematologist discordance changed after a consultation with a hematologist, and factors associated with persistent discordance. Methods Before and after consultation with a hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that patients tend to harbor an inaccurate expectation of cure, and this may be associated with poor satisfaction with cancer care. [30][31][32] Several limitations should be noted. First, recruitment of patients through social media may have introduced bias, considering the high prevalence of women in this study despite RCC being more common in men than women.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients tend to harbor an inaccurate expectation of cure, and this may be associated with poor satisfaction with cancer care. [30][31][32] Several limitations should be noted. First, recruitment of patients through social media may have introduced bias, considering the high prevalence of women in this study despite RCC being more common in men than women.…”
Section: Discussionmentioning
confidence: 99%
“…Limited integration of primary and specialty palliative care for patients with aggressive lymphoma contributes to prognostic discordance between patients and hematologic oncologists and impairment in QOL. 7,8 Among several barriers to palliative care (Table 1), one that is amplified for patients with relapsed/refractory aggressive lymphomas is high prognostic uncertainty, given the potential of cure in relapsed settings and recent treatment advances. 25,26 For example, although the SCHOLAR-1 trial results were sobering with complete response and 24-month overall survival of 7% and 20%, respectively, for patients with refractory DLBCL, 27 complete response ranges from 40% to 58% with chimeric antigen receptor (CAR) T-cell therapy, 25,26 and the estimated 24-month overall survival is 50.5% for axicabtagene ciloleucel.…”
Section: Benefits Of Palliative Carementioning
confidence: 99%
“…These patients have significant palliative care needs, including high physical and psychological symptom burden and impaired quality of life (QOL). [3][4][5] In addition, many harbor misunderstandings regarding their prognosis, [6][7][8] hindering their ability to engage in informed decision making regarding their care and end-of-life (EOL) preferences. Integrating high-quality palliative care is thus essential for this population; yet, existing evidence suggests suboptimal palliative care uptake.…”
Section: Introductionmentioning
confidence: 99%
“…For the patient model, we prespecified the inclusion of patient age, sex, race, and education level, regardless of the significance level, based on prior literature demonstrating the association of these variables with prognostic estimates. 32,37,44,45 For the caregiver model, we prespecified the inclusion of caregiver age, sex, race, and education level, regardless of significance level, based on rationale similar to that used in the patient model. We considered 2-sided P values <.05 statistically significant based on the exploratory nature of this study.…”
Section: Statistical Analysesmentioning
confidence: 99%